Upregulating microRNA‐210 to Inhibit Apoptosis of Neural Stem Cells with an MRI–Visible Nanomedicine for Stroke Therapy. Issue 9 (24th June 2022) - Zhang, Qinyuan; Cai, Jiali; Wang, Zhiyong; Wang, Zhe; Lin, Bingling; Zhao, Junya; Mao, Jiaji; Li, Yunhua; Li, Jianing; Yang, Xieqing; Shuai, Xintao; Lu, Liejing; et al.
Abstract : Transplantation of neural stem cells (NSCs) is a promising paradigm for treating stroke. However, the poor survival of transplanted NSCs greatly limits the therapeutic potential. microRNA‐210 (miR‐210), a key hypoxia‐regulated miRNA, can enhance cell survival by targeting the expression of multiple apoptosis‐related genes, such as caspase‐8‐associated protein‐2 (casp8ap2), Bax, and Bcl‐2. Meanwhile, a noninvasive cell‐tracking method is also indispensable for monitoring the in vivo cell‐based therapy. Herein, an MRI–visible nanomedicine is developed to codeliver superparamagnetic iron oxide (SPIO) nanoparticles and miR‐210 into NSCs. This therapeutic nanomedicine not only promotes the survival of NSCs via upregulating miR‐210 to inhibit NSCs apoptosis but also allows an in vivo tracking of transplanted NSCs with MRI. The enhanced NSCs survivability significantly promotes the structural and functional recovery after stroke onset, which highlights the great potential of the multifunctional nanomedicine to improve the therapeutic efficacy of NSCs for stroke treatment. Abstract : The microRNA‐210 (miR‐210)‐complexed, superparamagnetic iron oxide (SPIO)‐loaded, fluorinated low‐molecular‐weight polyethyleneimine‐based micelles (miRmimi‐SPIO/PEI‐F) can efficiently deliver miR‐210 into neural stem cells (NSCs) to inhibit the apoptosis via upregulating miR‐210. This magnetic resonance imaging (MRI)–visible nanomedicine can enhance structural and functional repair of NSCs in mouse model of acute ischemia stroke and allow in vivo tracking of NSCs with MRI.